2010
DOI: 10.1074/jbc.m110.114793
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Epicatechin Gallate into the Cytoplasmic Membrane of Methicillin-resistant Staphylococcus aureus Disrupts Penicillin-binding Protein (PBP) 2a-mediated β-Lactam Resistance by Delocalizing PBP2

Abstract: Epicatechin gallate (ECg) sensitizes methicillin-resistant Staphylococcus aureus (MRSA) to oxacillin and other β-lactam agents; it also reduces the secretion of virulence-associated proteins, prevents biofilm formation, and induces gross morphological changes in MRSA cells without compromising the growth rate. MRSA is resistant to oxacillin because of the presence of penicillin-binding protein 2a (PBP2a), which allows peptidoglycan synthesis to continue after oxacillin-mediated acylation of native PBPs. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 58 publications
4
96
0
Order By: Relevance
“…It has been proposed that damage inflicted to cell wall peptidoglycan is the main source of the stimuli to which VraR responds due to the tight control of VraS on the phosphorylation state of VraR (1). In addition, radiolabeling has shown that epicatechin gallate (ECG) binds predominantly to the CM, inducing an increase in its fluidity which results in uncoupling of some cell wall components that then cause delocalization of PBP2; as a consequence, the cells become more sensitive to beta-lactams and oxacillin (3). The structural similarity between ECG and EGCG and their common antimicrobial properties (33) tempt us to suggest that binding of EGCG to CM and relocation of PBP2 might be an additional mechanism conferring tolerance to beta-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that damage inflicted to cell wall peptidoglycan is the main source of the stimuli to which VraR responds due to the tight control of VraS on the phosphorylation state of VraR (1). In addition, radiolabeling has shown that epicatechin gallate (ECG) binds predominantly to the CM, inducing an increase in its fluidity which results in uncoupling of some cell wall components that then cause delocalization of PBP2; as a consequence, the cells become more sensitive to beta-lactams and oxacillin (3). The structural similarity between ECG and EGCG and their common antimicrobial properties (33) tempt us to suggest that binding of EGCG to CM and relocation of PBP2 might be an additional mechanism conferring tolerance to beta-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…As there is an inverse relationship between the intensity of polarized light emitted and fluidity of membrane, the effect of emodin on membrane fluidity was investigated by measuring fluorescence polarization of DPH inserted into the cell membrane (Bernal et al 2010). Briefly, MRSA252 (1.0× 10 6 CFU/mL) was treated with broth; 0.2 % DMSO (vehicle); 0.5, 1, and 2 μg/mL of emodin for 12 h with shaking of 150 rpm at 37°C.…”
Section: Cell Membrane Labeling and Fluorescence Anisotropy Measurementmentioning
confidence: 99%
“…It is part of the core cell wall stimulon (26). Its expression level is elevated by the presence of cell wall inhibitors and knockout of genes that are directly involved with peptidoglycan biosynthesis (3,23,26,27,42,46). Furthermore, inactivation of fmtA results in a lack of WTAs on S. aureus cell walls and deficiency in biofilm production (4,44).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the genome-wide S. aureus response to cell wall inhibitors have demonstrated that their biological activity causes upregulation of fmtA (3,26,27,41,46). In addition, inactivation of genes involved with cell wall biosynthesis, such as murF, leads to higher levels of fmtA (41).…”
mentioning
confidence: 99%